Rhodocyclus gelatinosus biomass for egg yolk pigmentation - Ponsano, EHG; Pinto, Marcos Franke [UNESP]; Neto, M. G.; Lacava, P. M. (Poultry Science Assoc Inc, 2004)
Biomass of the photosynthetic bacterium Rhodocyclus gelatinosus was used at different levels in laying hens' rations as a xanthophyll source. Sixty-four hens were used in the experiment that investigated the effects of different biomass concentrations on weight gain, egg production, egg weight, and yolk color as compared with a control group that received no biomass supplementation in the ration. Yolk color was scored by means of a color fan. All concentrations tested were able to provide yolk color scores higher than those provided by the control group. The pigment deposition began after 24 h of administration and reached a plateau around the twentieth day. Each increase in the supplementation level led to an additional increase on yolk color scores. Yolk colors of all treatments that received R. gelatinosus biomass differed significantly from the control group and from each other, corroborating that the increase in the biomass supplementation had a positive effect on color increase. Body weight loss occurred in all treatments. Egg production did not increase with the biomass addition, while a significant increase in egg weight was observed in the treatments that received the product.
Keywords: Rhodocyclus gelatinostis; biomass; laying hens; oxycarotenoids; yolk color; egg production; egg weight